Corporate Social Responsibility and Tax Avoidance: Evidence from Indonesia - Wahyu Agus Winarno; Alwan Sri Kustono; Rochman Effendi; Imam Mas'ud; Oktaviani Ari Wardhaningrum (AKRUAL: JURNAL AKUNTANSI, 2021)
This study examines the effects of state equity ownership on the relationship between corporate social responsibility investment and tax avoidance. Using a 474 firm-year observation sample of Indonesian companies from 2015 to 2018, we use the ordinary least square and subgroup analysis regressions to estimate the model with various proxies for tax avoidance. The results show that the companies with higher CSR investment have lower tax avoidance behavior in various proxies. In other words, companies with higher social responsibility performance will make lower tax savings. Furthermore, companies with state equity ownership have a lower relationship between CSR spending activities and tax avoidance than nonSEO companies. This research has several implications: First, this study uses total CSR expenditure as a proxy for CSR investment. Further research can create categories based on the type or dimension of CSR. Second, the research sample for state equity ownership is very small, and the next research can use a paired sample. This paper highlights the implication of CSR investment on taxation in Indonesia, and its findings have implications for regulators. Regulators can encourage the company's CSR activities, but the impact of these activities may differ depending on each company's motives, especially tax avoidance.